Dynamics of a Discrete Allelopathic Phytoplankton Model with Infinite Delays and Feedback Controls - Liang Zhao; Bin Qin; Fengde Chen (Discrete Dynamics in Nature and Society)
A discrete allelopathic phytoplankton model with infinite delays and feedback controls is studied in this paper. By applying the discrete comparison theorem, a set of sufficient conditions which guarantees the permanence of the system is obtained. Also, by constructing some suitable discrete Lyapunov functionals, some sufficient conditions for the extinction of the system are obtained. Our results extend and supplement some known results and show that the feedback controls and toxic substances play a crucial role on the permanence and extinction of the system.